Generation Z Purchasing Behavior Profile in the Digital Economy: Normative Analysis in Online Markets - Zhulal, Muhammad; Marits, Shofi Arofatul; Herman, Sebastian (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This research aims to detail Generation Z's purchasing behavior in the online market. This research provides an in-depth view for e-commerce companies and marketers to develop more effective strategies in attracting and retaining Generation Z. This research method is normative descriptive research. The type of research used is exploratory research. Data collection techniques involve literature reviews from various journal sources and related literature. The data analyzed is secondary data and the data analysis method involves normative analysis to identify the differences between "das sollen" (should) and "das sein" (actual conditions) in the purchasing behavior of Generation Z in the digital economy. This research reveals that Generation Z has a high affinity for using smartphones when shopping online, indicating a dependence on mobile technology in the digital economy era. Generation Z is more active in shopping online compared to previous generations, indicating the important role of digital platforms in shopping behavior patterns. Continuous recommendations from this research emphasize the importance of continuous adaptation to technological changes and the dynamics of Generation Z consumer behavior. Businesses are expected to combine innovative marketing strategies with responsive shopping experiences to attract and retain Generation Z as loyal consumers.